Engendering development : through gender equality in rights, resources, and voice. - World Bank. (Washington, D.C. : World Bank ; New York : Oxford University Press, 2001)
The book brings together existing and new research from several social science disciplines to examine the costs of persistent gender disparities to well-being and countries' development prospects.
Includes bibliographical references (p. 321-357) and index.
rua 30/04/15
Loans
Keywords: Sex role -- Developing countries; Women in development -- Developing countries